The mighty metaphor: a collection of therapists' favourite metaphors and analogies. (12th December 2016) - Killick, Steve; Curry, Vicki; Myles, Pamela
Abstract: Metaphor is a central tool of the therapist of many therapeutic modalities, and they are a particular feature of CBT. Metaphors can be essential tools in the therapeutic process; providing the therapist with a means of communicating potentially complex psychological concepts and theory to clients, and also being part of the process of change. This paper presents a series of metaphors that some of the most experienced and innovative practitioners in the world of CBT have found to be helpful. Each practitioner describes how to utilize the metaphor skilfully and effectively: providing some tips for facilitating both the presentation of metaphors to, and eliciting of metaphors from the client; and demonstrating how the use of metaphor can facilitate therapeutic change. Overall, the small selection of metaphors presented here demonstrate the great versatility of metaphor to address all kinds of issues in therapy, with a range of client groups and presenting difficulties; and how the shared exploration and collaboration of both client- and therapist-generated metaphors can be an important addition to the therapist's toolbox.